Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{m = \dfrac{\Delta_Y}{\Delta_X} = \dfrac{y_B - y_A}{x_B - x_A} = \dfrac{6 - 3}{6 - 3} = \dfrac{3}{3} = 1}[/tex]
[tex]\mathsf{y - y_0 = m(x - x_0)}[/tex]
[tex]\mathsf{y - 3 = 1(x - 3)}[/tex]
[tex]\mathsf{y - 3 = x - 3}[/tex]
[tex]\boxed{\boxed{\mathsf{y = x}}}\leftarrow\textsf{letra A}[/tex]
[tex]a = \frac{yb - ya}{xb - xa} = \frac{6 - 3}{6 - 3} = \frac{3}{3} = {\boxed{\sf \ 1}}[/tex]
[tex]y = ax + b \\ y = x + b \\ 3 = 3 + b \\ b = 3 - 3 \\ {\boxed{\sf \ b = 0}}[/tex]
- Portanto,a equação desta reta é:
[tex]{\boxed{\sf \ \red{y = x}}}[/tex]
espero ter ajudado!